YM155 Restores the Effect of Imatinib in Imatinib-Resistant Chronic Myeloid Leukemia Cell Lines - Al-Husein, Belal A.; Ahmad, Mohammad A. Bani; Nofal, Rand M.; Alqudah, Mohammad A. Y. (Current Cancer Drug Targets, 2025)
<span class=
Keywords: survivin inhibitor